Parameters of the Immune System and Vitamin D Levels in Old Individuals - Alves, Amanda Soares; Ishimura, Mayari Eika; Duarte, Yeda Aparecida de Oliveira; Bueno, Valquiria (Frontiers in Immunology, 2018)
Aim The increased number of individuals older than 80 years, centenarians, and supercentenarians is not a synonym for healthy aging, since severe infections, hospitalization, and disability are frequently observed. In this context, a possible strategy is to preserve the main characteristics/functions of the immune system with the aim to cause less damage to the organism during the aging process. Vitamin D acts on bone marrow, brain, breast, malignant cells, and immune system and has been recommended as a supplement. We aimed to evaluate whether immune parameters and vitamin D serum levels are correlated. Methods We evaluated some features of the immune system using the peripheral blood of individuals older than 80 years (n = 12) compared to young subjects (n = 10). In addition, we correlated these findings with vitamin D serum levels. Results Old individuals presented metabolic parameters of healthy aging and maintained preserved some features of immunity such as CD4/CD8 ratio, and low production of pro-inflammatory cytokines after stimulus. On the other hand, we observed increase in the frequency of myeloid-derived suppressor cells, reduction in circulating leukocytes, in the percentage of total CD8+, and in CD8+ Naïve T cells, in addition to increase in the percentage of CD8+ effector memory re-expressing CD45RA (EMRA) T cells. We found seropositivity for CMV in 97.7%, which was correlated with the decrease of CD8+ Naïve T cells and increase in CD8+ EMRA T cells. Vitamin D levels were insufficient in 50% of old individuals and correlated positively with total CD8+ T cells and negatively with CD8+ EMRA T cells. Conclusion In the studied population, longevity was correlated to maintenance of some immune parameters. Considering the limitations of the study as size of the sample and lack of functional assays, it was found that vitamin D in old individuals was correlated to some features of the immune system, mainly in the CD8 compartment.